The INTUIT Study: Investigating Neuroinflammation Underlying Postoperative Cognitive Dysfunction. Issue 4 (23rd January 2019) - Berger, Miles; Oyeyemi, Deborah; Olurinde, Mobolaji O.; Whitson, Heather E.; Weinhold, Kent J.; Woldorff, Marty G.; Lipsitz, Lewis A.; Moretti, Eugene; Giattino, Charles M.; Roberts, Kenneth C.; Zhou, Junhong; Bunning, Thomas; et al.
Abstract : BACKGROUND/OBJECTIVES: Every year, up to 40% of the more than 16 million older Americans who undergo anesthesia/surgery develop postoperative cognitive dysfunction (POCD) or delirium. Each of these distinct syndromes is associated with decreased quality of life, increased mortality, and a possible increased risk of Alzheimer's disease. One pathologic process hypothesized to underlie both delirium and POCD is neuroinflammation. The INTUIT study described here will determine the extent to which postoperative increases in cerebrospinal fluid (CSF) monocyte chemoattractant protein 1 (MCP‐1) levels and monocyte numbers are associated with delirium and/or POCD and their underlying brain connectivity changes. DESIGN: Observational prospective cohort. SETTING: Duke University Medical Center, Duke Regional Hospital, and Duke Raleigh Hospital. PARTICIPANTS: Patients 60 years of age or older (N = 200) undergoing noncardiac/nonneurologic surgery. MEASUREMENTS: Participants will undergo cognitive testing before, 6 weeks, and 1 year after surgery. Delirium screening will be performed on postoperative days 1 to 5. Blood and CSF samples are obtained before surgery, and 24 hours, 6 weeks, and 1 year after surgery. CSF MCP‐1 levels are measured by enzyme‐linked immunosorbent assay, and CSF monocytes are assessed by flow cytometry. Half the patients will also undergo pre‐ and postoperative functional magnetic resonance imaging scans. 32‐channel intraoperative electroencephalogram (EEG) recordings will be performed to identify intraoperative EEG correlates of neuroinflammation and/or postoperative cognitive resilience. Eighty patients will also undergo home sleep apnea testing to determine the relationships between sleep apnea severity, neuroinflammation, and impaired postoperative cognition. Additional assessments will help evaluate relationships between delirium, POCD, and other geriatric syndromes. CONCLUSION: INTUIT will use a transdisciplinary approach to study the role of neuroinflammation in postoperative delirium and cognitive dysfunction and their associated functional brain connectivity changes, and it may identify novel targets for treating and/or preventing delirium and POCD and their sequelae. J Am Geriatr Soc 67:794–798, 2019.